2006
DOI: 10.2106/jbjs.e.00332
|View full text |Cite
|
Sign up to set email alerts
|

Plate Fixation of Ununited Humeral Shaft Fractures

Abstract: Therapeutic Level III. See Instructions to Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(114 citation statements)
references
References 24 publications
4
102
0
4
Order By: Relevance
“…Many biological and biophysical interventions have been used in an attempt to accelerate fracture healing times including the use of bone graft substitutes [4,5], application of exogenous local recombinant growth factors [6,7], gene therapy [8], or tissue engineering approaches with biodegradable scaffolds [9,10]. Several modalities have gone on to be clinically useful such as recombinant growth factors, but high costs continue to preclude routine clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Many biological and biophysical interventions have been used in an attempt to accelerate fracture healing times including the use of bone graft substitutes [4,5], application of exogenous local recombinant growth factors [6,7], gene therapy [8], or tissue engineering approaches with biodegradable scaffolds [9,10]. Several modalities have gone on to be clinically useful such as recombinant growth factors, but high costs continue to preclude routine clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…(22) Several studies have reported their success in the treatment of aseptic humeral nonunion. (23)(24)(25)(26)(27) These studies only showed a stereotyped pattern of treatment and mostly described the results of plating with bone grafting. In contrast, we have applied an analytical approach to treatment of nonunion and based our treatment only on "what is necessary" .…”
Section: Discussionmentioning
confidence: 99%
“…In order to have enough stability at the non-union site, double plating, one on the lateral side and one on the posterior side is recommended [7]. Bone grafting is offered to enhance the biological environment [8].…”
Section: Discussionmentioning
confidence: 99%